Netflix Platform Binge Watching and its Relationship to Narrative Transportation Among Saudi Youth - Mahnabi, Amal Ali; Aljasir, Shua'a Abdulrahman (Journal of Humanities & Social Sciences, 2024)
The current study aimed to explore the extent of binge-watching on Netflix platform among a sample of Saudi youth and examine its relationship with narrative transportation. Additionally, the study sought to identify the demographic differences in binge-watching behavior.To achieve these goals, the study employed a quantitative approach. An electronic questionnaire was administered to collect data from a purposive sample and a snowball sample, consisting of 388 Saudi young men and women.The study revealed several important results. Over half of the Saudi youth sample engage in a binge-watching session one to three times a week, categorizing them as regular binge-watchers. Additionally, more than 20% of the sample binge-watch more than three times a week, classifying them as heavy binge-watchers. The frequency of binge watching is influenced by both age group and educational level, while narrative transportation is also affected by age group. Besides, there are statistically significant differences in narrative transportation based on the levels of binge-watching intensity.
Keywords: Binge-Watching; Netflix; Narrative Transportation; Saudi Youth